Knowledge, innovation and the race to the South Pole. (16th August 2022) - Savitt, Ronald; Lüdecke, Cornelia
Abstract: The present article extends recent studies that ask what might else have been considered by Scott and Amundsen in planning their sledging operations to reach the South Pole during the southern summer of 1911/12. Both were on the cusp of changes in exploration methods and had at hand significant knowledge from past expeditions. Scott's preparations were based on British Arctic experiences using several haulage methods including the recent innovation, motor sledges. He had little success with them although more research and experimentation might have made them valuable. Amundsen's integrated program was based on previous American and Norwegian exploration in the Arctic and Antarctica. The race was between two men with very different backgrounds. Scott and Amundsen belonged to the same generation, Scott followed the romantic tradition of heroism as suffering; whereas Amundsen came from a culture that did not value unnecessary risk to life and limb. He won the race with a different organizational type and a different approach to gathering and using knowledge. Evolutionary economics with its focus on organizational structure and its impact on the use of knowledge and innovation is used to evaluate the plans and results of Scott and Amundsen.